Reversible stimuli-responsive luminescence of bimetallic cuprous complexes based on NH-deprotonated 3-(2′-pyridyl)pyrazole. Issue 46 (15th November 2021) - Tong, Yang; Chen, Xing-Wei; He, Li-Hua; Chen, Jing-Lin; Liu, Sui-Jun; Wen, He-Rui
Abstract : Reversible stimuli-responsive luminescence virtually stems from the breaking and rebuilding of various CH⋯O hydrogen bonds around ClO4 −, as supported by single-crystal analysis, the 1 H NMR spectra, and the PXRD and FT-IR spectra in various forms. Abstract : Color regulation of solid-state luminescence is desirable and challenging. Herein, we report two new three- and four-coordinate bimetallic cuprous complexes 1 and 2, which bear a NH-deprotonated 3-(2′-pyridyl)pyrazole adopting the monoanionic tridentate μ-η 1 (N)η 2 (N, N) bonding mode and exhibit reversible stimuli-responsive luminescence. It is revealed that the reversible stimuli-responsive luminescence for 1 and 2 is triggered by the destruction and restoration of orderly molecular stacking, along with the loss and recovery of the CH2 Cl2 solvent molecules for 1 . Virtually, this reversible stimuli-responsive luminescence originates from the breaking and rebuilding of various CH⋯O hydrogen bonds around ClO4 −, as supported by X-ray single-crystal analysis, the 1 H NMR spectra, and the PXRD and FT-IR spectra in various forms. In addition, the possible applications of this reversible stimuli-responsive luminescence have also been investigated.